Pengaruh Pendidikan Pajak, Sosialisasi Pajak, Dan Sanksi Perpajakan Terhadap Kepatuhan Kewajiban Perpajakan - Pricillia, Angeline; Subagyo (Jurnal Penelitian Teori & Terapan Akuntansi (PETA), 2025)
Tax is one of the state revenues that will be used as national development. However, tax revenues in the country are still not optimal because the level of taxpayer compliance is still low. This study aims to examine the influence of tax education, tax socialization, and tax sanctions of compliance with tax obligations. In this study author uses a sampling technuques were carried aut using the non-probability sampling method. The data was obtained by distributing questionnaires to taxpayer in DKI Jakarta and processed using SPSS version 25. The influence of tax education, tax socialization, and tax sanctions in increasing taxpayer positive effected on compliance with tax obligations.